Periodontite apical e saúde sistêmica: interações com substâncias nocivas e estratégias imunomoduladoras - Ferraz, Danilo Cassiano (2024)
The overall objective of this study was to explore apical periodontitis (AP), an osteolytic chronic inflammatory disease with significant local and systemic consequences. Chapter 1 examines the relationship between AP and oxidative stress, both locally and systemically, highlighting how this inflammatory condition can contribute to the worsening of systemic diseases such as diabetes and cardiovascular disorders. Reviewed studies show that reactive oxygen species (ROS) exacerbate inflammation and impair immune responses, while appropriate endodontic treatment can reduce oxidative stress, benefiting both local and systemic health. In Chapter 2, a bibliometric analysis identifies the 100 most-cited articles on AP and systemic health, demonstrating the growing interest in the relationship between these areas. This analysis highlights key articles, institutions, and topics studied, such as associations between AP and systemic diseases. Most of the reviewed articles were published in high-impact journals, particularly in Europe and Latin America, underscoring the importance of AP in overall health and the need for interdisciplinary approaches. Chapter 3 investigates the effects of secondhand smoke (ShS) exposure on AP progression and lung health. Using a Wistar rat model (n=7), the study revealed an exacerbation in AP development when associated with ShS, as observed through micro-computed tomography (p<.05). This association also showed an increase in oxidative stress (p<.05) in lung tissue, as well as significant morphological changes (p<.05), including alveolar destruction and airway remodeling. These findings indicate that ShS exposure can worsen both oral and systemic manifestations of AP, emphasizing the importance of considering environmental factors in oral and systemic health management. Chapter 4 explores the effects of alcohol and ShS on antioxidant activity and morphological changes in liver tissue of rats with AP (n=7). The results indicate that AP, when combined with alcohol consumption or ShS exposure, compromises liver antioxidant capacity (p<.05) and promotes sinusoidal space dilation (p<.05). These findings suggest that AP, when associated with harmful habits, may intensify hepatic dysfunction. Data from Chapters 3 and 4 were analyzed using one-way ANOVA, followed by multiple comparisons with Tukey and Dunnett tests (α=.05). Chapter 5 14 investigates the use of the C-C motif chemokine ligand 2 (CCL2) as an immunomodulatory therapy in a simulated in vitro AP environment with LPS- induced inflammation. Cell proliferation was measured by the CCK-8 assay, while gene expression relevant to AP was evaluated using RT-qPCR. Gene expression levels were calculated by the 2−ΔΔCt comparative method. In co-culture of mesenchymal stem cells from the periodontal ligament (PDLSCs) and apical papilla (SCAPs), CCL2 demonstrated the ability to modulate the inflammatory response, promoting the expression of osteogenic and inflammatory genes without affecting cell proliferation (p>.05). These results suggest that CCL2 may have a protective role in tissue repair by mediating the immune response, representing a promising therapeutic approach for AP treatment.